Special Autonomy Fund Management and Strengthening Institutional Governance in Realizing Sustainable Development - Dahlawi Dahlawi; Helmi Helmi; Ade Mardiya Qahar; Nurul Fajri; Mukhrijal Mukhrijal; Nurul Kamaly; Afrijal Afrijal; Nofriadi Nofriadi (Journal of Governance and Public Policy, 2023)
Granting special autonomy to Aceh Province is the government's response to support sustainable development in post-conflict. This study aims to optimize the management of Otsus funds for the overall welfare of the Acehnese people, with the ultimate goal of achieving independence. This study focuses on explaining and addressing issues related to managing the special autonomy fund and strengthening institutions to realize sustainable development and prosperity for the Acehnese. Descriptive qualitative research methodology was employed, involving data collection, reduction, presentation, and conclusion. The analysis utilizes the accountability and transparency theory to evaluate fund management practices in Aceh. Findings revealed that the special autonomy fund has not been effectively implemented due to weak institutional capacity, hindering sustainable development and welfare. Transparent fund management aligned with good governance has not been optimally achieved. The dominance of local political elites in policy-making has led to ineffective government management of the special autonomy fund, while bureaucratic efforts have yielded limited results. Nonetheless, Aceh has undergone some changes over the past 15 years, although not yet significant.